2017
DOI: 10.1080/09540121.2017.1327646
|View full text |Cite
|
Sign up to set email alerts
|

HIV-infected individuals who use alcohol and other drugs, and virologic suppression

Abstract: People living with HIV (PLWH) on antiretroviral therapy (ART) who use substances were examined to (a) describe those with virologic control and (b) determine which substance use-factors are associated with lack of virologic control. Participants were adult PLWH taking ART with either past 12-month DSM-IV substance dependence or past 30-day alcohol or illicit drug use. Substance use factors included number of DSM-IV alcohol or drug dependence criteria and past 30-day specific substance use. Associations with HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 51 publications
3
28
1
Order By: Relevance
“…Of note, in many of these same studies [24, 26, 27, 25], cannabis use was not a risk for suboptimal ART adherence. This lack of association between cannabis use and ART adherence was also documented in other recent analyses [3032].…”
Section: Specific Substances and Art Adherencementioning
confidence: 93%
See 2 more Smart Citations
“…Of note, in many of these same studies [24, 26, 27, 25], cannabis use was not a risk for suboptimal ART adherence. This lack of association between cannabis use and ART adherence was also documented in other recent analyses [3032].…”
Section: Specific Substances and Art Adherencementioning
confidence: 93%
“…A recent review examining the impacts of alcohol on the HIV cascade of care continuum published between 2010 and 2015 found an association between alcohol use and nonadherence, usually in a dose-response fashion, in most (n=16) of the 33 included studies focusing on the ART adherence step [22]. Other recent studies confirm this negative influence of alcohol on ART adherence in a variety of contexts [23, 17, 24, 25]. …”
Section: Specific Substances and Art Adherencementioning
confidence: 99%
See 1 more Smart Citation
“…These findings highlight the need for more attention to those who trade sex and use drugs. In the absence of treatment, research has shown that alcohol and substance use has a negative effect on ART adherence and subsequent viral suppression, emphasizing likely consequences of not utilizing substance use treatment among PLWH engaged in sex trade [70]. …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HIV-infected and HIV/hepatitis c virus-coinfected patients in opiate replacement therapy require higher methadone dose [20]. Among drug users, the analysis of HIV infection and prevention presents a relationship between drug-use and men-who-have-sex with other men, sexual behavior and sexually-transmitted diseases [21][22][23].…”
Section: Editorialmentioning
confidence: 99%